Recurrent Optic Perineuritis after Intranasal Cocaine Abuse. (April 2014) - Coppens, S.; Petzold, A.; de Graaf, P.; de Vries-Knoppert, W. A. E. J.
Abstract Recurrent optic perineuritis can be related to orbital inflammation. Here we present the case of a 46-year-old male patient in whom recurrent episodes of optic perineuritis were related to chronic osteolytic sinusitis following intranasal cocaine abuse. Magnetic resonance imaging (MRI) demonstrated optic perineuritis adjacent to a soft tissue mass that intruded the orbit from the nasal cavity. Computed tomography (CT) confirmed destruction of the medial orbital wall. Staphylococcus aureus was cultured and biopsy showed granulomatous tissue. Visual outcome was poor. We review the literature and discuss the diagnostic pitfalls and management implications in relation to optic (peri)neuritis originating from the nasal sinuses.